Death, denial and dissidents: white commercial farmers’ discursive responses to mass violence in Zimbabwe, 1970-1980 - Pilossof, Rory (University of the Free State, 2015)
This article investigates how white farmers in Zimbabwe reacted to two violent episodes in Zimbabwe’s recent history: the liberation war in the 1970s and the violence of Gukurahundi in the 1980s. The foregrounding of violence against white farmers by white farming representatives and mouthpieces in the 1980s was in direct contrast to the almost complete lack of acknowledgement of ‘terrorist’ casualties during the liberation war, and was a deliberate strategy on behalf of white farmers to recast themselves as an ‘endangered’ species that needed government protection. This article analyses how the discursive strategies of narrative violence changed for white farmers from the 1970s to the 1980s. The changing social and political contexts meant that white farmers had to adapt the tactics employed for narrating and discussing violence, with silencing and selective remembering as key components throughout this troubled period.
Keywords: White farmers; Zimbabwe; Liberation war; Violence